Roles of TRAFs in Ischemia-Reperfusion Injury - Zhou, Wei; Lin, Danni; Zhong, Zibiao; Ye, Qifa (Frontiers in Cell and Developmental Biology, 2020)
Tumor necrosis factor receptor-associated factor (TRAF) proteins are a family of signaling molecules that function downstream of multiple receptor signaling pathways, and they play a pivotal role in the regulation of intracellular biological progresses. These TRAF-dependent signaling pathways and physiological functions have been involved in the occurrence and progression of ischemia-reperfusion injury (IRI), which is a common pathophysiological process that occurs in a wide variety of clinical events, including ischemic shock, organ transplantation and thrombolytic therapy, resulting in a poor prognosis and high mortality. IRI occurs in multiple organs, including liver, kidney, heart, lung, brain, intestine and retina. In recent years, mounting compelling evidence has confirmed that the genetic alterations of TRAFs can cause subversive phenotype changes during IRI of those organs. In this review, based on current knowledge, we summarized and analyzed the regulatory effect of TRAFs on the IRI of various organs, providing clear direction and a firm theoretical basis for the development of treatment strategies to manipulate TRAF proteins or TRAF-dependent signaling pathways in IRI-related diseases.